Child Abuse in Damian Robin’s Poems Grooming, Victims, and Child Abuse (2016), Jim Farrell’s Poems Fetus (2022), and Weaned on Poison (2021) - Ulul Azmi, Rahmad Aulia; Al Hafizh, Muhammad (Universitas Negeri Padang, 2023)
There are many problems that have been created due to child abuse that have been resolved from the past until now. Starting from the physical and psychological impacts that can have short-term and long-term impacts and can be passed on to the next generation which makes child abuse a social problem that does not end. In understanding this case, the researcher uses a descriptive quailtative technique with a psychoanalysis approach to analyze Damian Robin’s poems with the title Grooming, Victims, and Child Abuse (2016), and poems written by Jim Farrel with the title Fetus (2022), and Weaned on Poison (2021). This research use life and death instinct theory by Sigmund Freud. The outcome of this study shows that there are seven causes of child abuse, four types of abuse suffered by the victims in the five poems. They are physical, emotional/verbal, sexual abuse, and neglect / abandonment. The effects of these abuse showed in life and death instinct that comes from within the victim.